In Silico Identification of Emblica officinalis Compounds Inhibiting Thermolabile Hemolysin from Vibrio alginolyticus in Shrimp - Bari, Sayed Mashequl; Marma, Meamaching; Reza, Nafees Bin; Ahmed, Sk. Faisal; Islam, Shoriful; Rayhan, Nafis; Hossian, Md. Alomgir; Rahman, Md. Matiur; Alam, Md. Saiful (Current Computer - Aided Drug Design, 2025)
BackgroundThermolabile hemolysin (TLH) is a key virulent protein of Vibrio alginolyticus, known for its hemolytic and phospholipase activities, leading to shrimp vibriosis disease. It has been suggested as a potential therapeutic candidate for vibriosis therapy.MethodsComputational studies, including molecular docking, toxicity analysis, and molecular dynamics (MD) simulations, were conducted to investigate the inhibition of the phospholipase activity of TLH by phytochemicals from Emblica officinalis.ResultsOut of the twenty-nine compounds, the top three, including Ellagic acid (CID 5281855), Quercetin (CID 5280343), and Kaempferol (CID 5280863), were sorted based on their highest molecular docking scores of -9.2, -8.9, and -8.8, respectively. Subsequently, molecular dynamics (MD) simulations of these selected leads were performed to observe the structural stability of these compounds in the binding sites of TLH protein. The MD simulation outcomes indicated that all three compounds demonstrated superior stability throughout 100 nanoseconds compared to the control compound Resveratrol. The molecular simulation results suggest stable interactions, with average root-mean-square deviation (RMSD) and root-mean-square fluctuation (RMSF) values of 1-2 Å and 0-3 Å. Pharmacokinetic and toxicity analyses were conducted to evaluate the suitability and toxicity of these selected compounds. All top three compounds passed the Lipinski rule, and toxicity criteria.ConclusionTherefore, these compounds have the potential to serve as effective therapeutics for controlling Vibrio alginolyticus infection in shrimp.
Keywords: ADMET